An Analysis Correlation And Dynamic Simulation Of Customer Engagement Value Through Green Supply Chain Management - Rohmah, Wafrotur; Nur Jamal, Fauziyah; Chairul Saleh, Raden; Aulia, Yunita; Suranto, Suranto (International Journal of Supply Chain Management, 2020)
As the existance of green products and services are increasing, the property industry is trying to develop their product such as green supply chain management concept. Most of the green supply chain management concept that offered by the property industry are including green environmental, waste management, water management and many others. The objectives of this research is to identify the value of customer engagement model. Conceptual model is developed to idenfity the relationship between the variables and its indicators (exogenous) which affecting the customer engagement value (endogenous). This relationship identification has been done by using Structural Equation Modeling. Although, the measurement of customer engagement value is conducted by using system dynamics simulation. The result of this research prove that the relationship of five exogenous variables  toward the endogenous are significant. Also, it is obtained the prediction value of customer engagement per unit of time.